Melancholy Secrets: Nietzsche in America - Jukić, Tatjana (2007)
In Untimely Meditations Nietzsche says that the very potentiality of transplanting a culture "to a foreign soil" depends on the rhythmic play of the Hellenic and the Oriental. One could argue however that Nietzsche's notion of culture in time, stemming seemingly from a rhythmicized binary between the Hellenic and the Oriental, derives actually from a pre-originary call to deconstruct even such binaries— a call that Nietzsche inherited in part from Emerson's writings and Emerson's view of America. In other words, one could argue perhaps that this rhythm is not calling for deconstruction as in some way anterior to deconstructing, but possibly traces a position where the pre-originary— configured in Nietzsche as a node of Emerson’ s America and what in deconstruction is philosophy’ s technology— is forgotten or articulated as forgettable. I would like to explore the scope of this oblivion, or possibly of this melancholia in Nietzsche, from within a turn where Nietzsche’ s philosophy works as legacy in the Americas of Gilles Deleuze and Stanley Cavell.